Pengaruh Dividen Inisiasi dan Dividen Omisi terhadap Return Saham di Bursa Efek Indonesia - Azizah Ayu Sielvia (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
The objective of this study is to determine the effect of dividend initiations and dividend omission of stock returns in Indonesia Stock Exchange (BEI). Variables in this study consist of dividends, dividend announcements, and a significant stock return on dividend announcement reflected the presence of abnormal return during the event period. This study employs the company's shares listed on Indonesia Stock Exchange and are actively traded. Samples used as many as 50 companies, where 37 companies as a dividend initiation and 13 companies as a dividend omission. The sample selection was done by purposive sampling method that is research based on certain criteria. Results of analysis testing the effect of the abnormal return of dividend announcements indicate a significant influence. Announcements of dividend initiations have significant positive influence, while the announcements of dividend omissions have significant negative market reaction. That means the announcement of dividend initiations have a signal or a specific information content that causes the market to react more than normal state of the information, while the announcement of dividend omissions affect investors to remove their stock price moves down or there is a significant abnormal return.Keywords: dividend initiation, dividend omission, dividend announcement, stock return